Anti-Inflammatory Activity of a Peptide from Skipjack (Katsuwonus pelamis) - Zhi-gao Wang; Xiao-guo Ying; Peng Gao; Chun-li Wang; Yi-fan Wang; Xin-wei Yu; Jing Chen; Bin Wang; Hong-yu Luo (Marine Drugs, 2019)
In this paper, the effect of skipjack (Katsuwonus pelamis) enzymatic peptide (SEP), which was prepared and purified from a byproduct of skipjack, on inflammation, ulcerative colitis and the regulation of intestinal flora was studied in a mouse ulcerative colitis model and a transgenic zebrafish inflammation model. The aggregation of transgenic granulocyte neutrophils in zebrafish from a normal environment and from a sterile environment was calculated, and the anti-inflammatory activity of SEP was evaluated. To evaluate the anti-ulcerative colitis activity of SEP, DSS-induced colitis mice were given SEP, salicylazosulfapyridine (SASP), or SASP + SEP. Then, the concentrations of IL-6, IL-10 and TNF-α in the serum were detected, the HE-stained colon tissue was examined by microscopy the species composition and abundance distribution of the intestinal flora was analyzed. The results showed that 500 μg/mL SEP treatment significantly alleviated neutrophil granulocyte aggregation in the zebrafish inflammation model; Diarrhea, hematochezia and body weight loss were alleviated to a certain extent in mice gavaged with SEP and SASP, and the combination of SASP with SEP was the most effective in mice. The damage to villi in the intestine was completely repaired, and the levels of IL-6, IL-10 and TNF-α, which are associated with inflammation, were all reduced. In addition, the proportion of intestinal probiotics or harmless bacteria increased, while that of pathogenic bacteria decreased, and the effect of the combined treatment was the most pronounced. These results show that SEP could relieve inflammation, cure ulcerative colitis, regulate intestinal flora and enhance the therapeutic effect of the clinical drug SASP. This study provides a theoretical basis for the development of SEP as an anti-inflammatory adjuvant therapy and intestinal flora regulator.